Price Determination for Educational Services Based on the Investments in Education - Blaga, Radu Lucian; Blaga, Alexandru (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2016)
The study aims at highlighting the link between educational marketing (product/service and price determination for educational services) and investment in education, using empirical models and customization of classic approaches (interpolation method) addressed to individual educational investment. The methodology discussed in the paper, considers essential invariants of these educational investments, such as seniority - part of the work experience and period of studies. In the models presented, the level and the period of studies are quantified through transferable credits, expressing units of time, normal volume of working alleged student learning. It is also used a parameter which introduces an essential element of the quality of work - the psycho-physical characteristics of the fellow that are correlated with age. Empirical study materializes on developing, while testing and validation of the models show that the rate of return to investment in education is a rationale for individuals to decide investing in their education. The study offers some customized recommendation to improve reverse marketing price policy of the educational services. The study results lead us to the conclusion that education providers (colleges, universities, other training entities) and clients should take into account that education is an investment. The private return of investment in education - as argument of educational marketing (price policy) is increasingly important in the context of a fragmentary and dynamic market, led by strong competition.